Prática do aleitamento materno e fatores sociodemográficos que influenciam o comportamento de mães surdas em comparação a mães ouvintes - Raquel Fabiane Nogueira de Jesus dos Santos (2020)
The practice of breastfeeding is important in the healthy development of the baby, participates in harmonious facial growth and prevents the installation of harmful oral habits that can compromise the child's oral health. The deaf community communicates through sign language and may encounter challenges in acquiring health information, unlike the hearing community. The aim of this study was to compare the behavior of deaf mothers and mothers heard on the factors that influence the practice of breastfeeding and care for their children. In this comparative cross-sectional study 1: 3, 29 deaf mothers and 87 listeners participated, totaling 116 mothers with children between 2 and 5 years old. Mothers were selected at the Reference Center for mothers while mothers were heard at two public daycare centers in Belo Horizonte, Brazil. A semi-structured questionnaire was applied addressing sociodemographic issues of the family, child development, gestational time, type of breastfeeding and nutritional sucking habits. To measure the anxiety level of the groups studied, use the Beck Anxiety Inventory (IAB) in versions valid for Brazilian Portuguese and for Brazilian Sign Language (Libras). Data collection was carried out for both groups of mothers. For statistical analysis, descriptive analyzes were performed, chi-square test with likelihood ratio, Kruskal-Wallis test (p <0.05) and Bonferroni correction (p≤0.008). The mothers' age range varied between 19-49 years, with a mean age of 31.5 years (+7.4). He found a statistically significant association between deaf mothers and an occurrence of premature birth (p = 0.003), anxiety level (P = 0.003) and bottle feeding (p = <0.001), these variables being more prevalent in this group. No group of mothers heard a statistically significant association only in the supply of a pacifier (p = 0.007), with an occurrence of premature birth and a lower level of anxiety in this group. It was concluded that there was a difference in behavior between the groups studied, with deaf mothers being more prone to preterm birth, more anxious during the practice of breastfeeding and more likely to offer a bottle than listeners